Investigating factors affecting tabarru’ funds of Sharia life insurance in Indonesia - Arini Lestari; Muhammad Lathief Ilhamy Nasution; Budi Harianto (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This research seeks to investigate the impact of claims, reinsurance, and operational expenses on the allocation of tabarru' funds within the context of Sharia-compliant life insurance in Indonesia.Method — This study employed a quantitative methodology, utilizing panel data regression analysis techniques. The dataset utilized in this investigation was acquired through a purposive sampling method, consisting of secondary data sources. The dataset employed by the researchers encompassed financial reports from Sharia-compliant life insurance companies spanning the period from 2018 to 2022. The sample for this scholarly endeavor comprised 14 Sharia life insurance firms duly registered with the Financial Services Authority (OJK).Result — The results of this investigation demonstrate that claims, Islamic reinsurance, and operational expenditures exert a noteworthy impact on the proportion of tabarru' funds.Contribution — The study delves into the factors impacting the proportion of tabarru’ funds in Sharia-compliant life insurance companies, which remains a relatively limited area of investigation, particularly across different countries.